问题 解答题
计算
(1)-16+23+(-17)-(-7)
(2)0-
1
2
-(-
3
4
)+(-
5
6
)-
2
3

(3)
2
5
÷(-2
2
5
)
-
8
21
×(-1
3
4
)
-0.5÷2×
7
2

(4)[2
1
2
-(
7
9
-
11
12
+
1
6
)×36]÷5.
答案

(1)-16+23+(-17)-(-7)

=-16+23-17+7

=-33+30

=-3;

(2)0-

1
2
-(-
3
4
)+(-
5
6
)-
2
3

=-

6
12
+
9
12
-
10
12
-
8
12

=-1

1
4

(3)

2
5
÷(-2
2
5
)
-
8
21
×(-1
3
4
)
-0.5÷2×
7
2

=-

1
6
+
2
3
-
1
2
×
1
2
×
7
2

=-

1
6
+
2
3
-
7
8

=-

3
8

(4)[2

1
2
-(
7
9
-
11
12
+
1
6
)×36]÷5

=[2

1
2
-(28-33+6)]÷5

=[2

1
2
-1]÷5

=

3
2
÷5

=

3
10

单项选择题
单项选择题